LEARNING FROM THE PAST TO PREPARE FOR THE FUTURE: A REVIEW OF RESEARCH OUTPUT ON POSTGRADUATE EDUCATION IN DESIGN AT THE FACULCITY OF VISUAL ART AND DESIGN, ITB (2015-2018) - Achmad Syarief; Yan Yan Sunarya (Jurnal Sosioteknologi, 2019)
Recent technological advancement and the betterment of socio-cultural welfare put design knowledge at the forefront of life as its practice develops into more than 'activity of making'. Rapid prototyping, 3D printing, internet-of-things, and wide array of networking channels may ease the burden of producing objects. For the past 20 years, the practice of design has addressed 'activity of research' beyond previous ordinary know-how in making object. Indonesia"”more specifically the postgraduate programme of the Faculty of Visual Art and Design, ITB"”has embedded research activities in design education since 1990s, yet there is no objective review on how this 'activity of design research' is managed and learned upon. To address this issue, this study was conducted through literature review by examining 327 master's degree theses in design program (2015-2018) using content analysis on approach, output, and focus of research. A thematic content analysis was applied to identify the intertwined relation on the context of the produced knowledge and approaches to strategies in design research as derived from those of graduates' thesis. By exploring master's degree thesis in design program, the paper exposes weaknesses and advantages on approaching research in design. The result encourages us to learn from our past experiences in conducting academic program and managing research in design to prepare for more applicable and suited design education with societal needs, which serves as the main contribution in the discussions.   Kemajuan teknologi baru-baru ini dan peningkatan kesejahteraan sosial-budaya menjadikan pengetahuan desain berada di garis depan kehidupan, karena praktiknya berkembang menjadi lebih dari sekedar 'aktivitas pembuatan. Prototipe, pencetakan 3 dimensi, internet untuk semua hal, dan beragam saluran jaringan yang berkembang dengan cepat dapat meringankan beban produksi objek. Selama 20 tahun terakhir, praktik desain telah membahas 'kegiatan penelitian' di luar pengetahuan biasa dalam membuat objek. Indonesia "”khususnya program pascasarjana Fakultas Seni Rupa dan Desain, ITB"” telah memasukkan kegiatan penelitian dalam pendidikan desain sejak tahun 1990-an, namun tidak ada ulasan objektif tentang bagaimana 'kegiatan penelitian desain' ini dikelola dan dipelajari. Untuk mengatasi masalah ini, penelitian dilakukan melalui tinjauan pustaka dengan menganalisis 327 tesis mahasiswa magister program desain (2015-2018) menggunakan analisis konten pada pendekatan, output, dan fokus penelitian. Analisis konten tematik diterapkan untuk mengidentifikasi hubungan yang saling terkait pada konteks pengetahuan yang dihasilkan dan pendekatan strategi dalam penelitian desain yang berasal dari tesis lulusan. Dengan menganalisis tesis mahasiswa magister program desain, penelitian ini memaparkan kelemahan dan kekuatan pendekatan penelitian di bidang desain. Hasil mendorong kami untuk belajar dari pengalaman masa lalu dalam menyelengkarakan program akademik dan mengelola penelitian di bidang desain, supaya pendidikan desain yang lebih sesuai dan cocok dengan kebutuhan masyarakat dapat dipersiapkan. Hal ini berfungsi sebagai kontribusi utama dalam penelitian ini.